Current status of dung beetles (Coleoptera, Scarabaeidae, Scarabaeinae) diversity and conservation in Natural Protected Areas in Chiapas (Mexico) - Gibrán Sánchez-Hernández; Benigno Gómez; Eduardo Rafael Chamé-Vázquez; Rolando A. Dávila-Sánchez; M. Edivaldo Rodríguez-López; Leonardo Delgado (Neotropical Biology and Conservation, 2020)
Natural Protected Areas (NPAs) are consider adequate tools for biodiversity conservation. Currently in Mexico there are 182 federal NPAs classified according to their management objectives. Chiapas is the Mexican state with the highest number of decreed NPAs and also allocates one of the largest territorial extensions for its protection. Unlike other taxa, and despite their proven ability to respond to ecosystem changes, the study of dung beetles within Mexican NPAs has been underestimated, as they are not considered as a priority group within their management and conservation programs. Based on the review of information available in publications and database on dung beetles, a list of 112 species and seven subspecies recorded in 16 of the 19 federal NPAs established in Chiapas is presented. The species recorded by each NPA show a significant correlation with the number of publications, but a low percentage of them correspond to studies with systematic samplings and most of the species reported in several of the NPAs come from sporadic records, which prevents the study of several basic and applied aspects of dung beetles in the region. Therefore, studies that extensively analyze the communities of arthropod groups, such as the Scarabaeinae, are necessary to understand their response to changes in the ecosystem at local and regional scale. It is advisable that these insects be included in the previous justifying studies for the designation or establishment of NPAs and, in turn, considered in the biological monitoring programs of these areas for their capacity as a bioindicator group.